WORK-LIFE BALANCE: A STUDY AMONG THE FEMALE NURSING PROFESSIONALS IN KOLLAM TOWN - Unnimaya P S
This study is about the female nursing professionals to know whether they are able to achieve better balance between their work life and personal life, to identify what are the facilitators and obstacles in creating a good work-life balance and to compare Work Life Balance between private and Govt. hospital nursing professionals. The research is carried out between selected Private and Government hospitals in Kollam town. A sample of 200 nursing professionals is included. Statistical analysis revealed that generally the nursing professionals are able to manage their work and personal life. But the study gives a different picture about the Government hospital nursing professionals. Results showed that the nursing professionals in private hospitals are better achieving work-life balance than that of the government hospitals.